Listen to the voice of the Earth learn about earthquakes to save lives - Oki, Satoko 1978-; Iwaki, Takako (Translator) (Tokyo Japan Publishing Industry Foundation for Culture, 2015)
A seismologist explains what causes earthquakes and how we can live with them to protect our lives.
Introduction. What happened on March 11, 2011? -- Ch. 1. What causes earthquakes? -- Ch. 2 Why earthquakes occur -- Ch. 3. What causes tsunamis? -- Ch. 4. The many effects of great earthquakes -- Ch. 5. How to become the earth's messenger -- Ch. 6. A journey to the center of the earth -- Ch. 7. The earth, a chatty hot planet -- Ch. 8. To save lives -- Some ideas for your earthquake research -- Further study -- Afterword.
"Originally published in Japanese language by Kumon Publishing Co., Ltd. in 2011"--Title page verso.
Includes bibliographical references (pages 137-138).
Keywords: Earthquakes -- Juvenile literature; Geophysics -- Juvenile literature; Earthquakes; Geophysics; Geophysik; Naturkatastrophe; Erdbeben; Okologie; Juvenile works